2014
DOI: 10.14257/ijbsbt.2014.6.3.07
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Closed Kinetic Chain Exercise Using EMG Biofeedback on PFPS Patients` Pain and Muscle Functions

Abstract: This study aimed to examine the effects of closed kinetic chain exercise using electromyography (EMG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The studies conducted by, 15,20,31 were demonstrated good quality (≥7), according to the cut-off points established earlier. Meanwhile the studies undertaken by [27][28][29]32 deemed to be of moderate quality (<7), whereas the studies by 26 and 11 were of poor quality (<4).…”
Section: Quality Of Evidencementioning
confidence: 82%
“…The studies conducted by, 15,20,31 were demonstrated good quality (≥7), according to the cut-off points established earlier. Meanwhile the studies undertaken by [27][28][29]32 deemed to be of moderate quality (<7), whereas the studies by 26 and 11 were of poor quality (<4).…”
Section: Quality Of Evidencementioning
confidence: 82%
“…According to many studies, it has been considered that weakness of the VMO muscle results in PFPS and that this condition is caused by an imbalance in activity between the VMO and the VL muscle 13 ) . In general, strengthening exercise for the quadriceps femoris muscle has been regarded as a common intervention for patients with PFPS in the field of physical therapy, and use of open kinetic chain exercise has been preferred 6 ) . However, open chain knee extension produces anterior shear force that induces stress in the patellofemoral joint.…”
Section: Discussionmentioning
confidence: 99%
“…Patellofemoral pain syndrome (PFPS), an overuse injury characterized by anterior knee pain, is a condition commonly diagnosed in young individuals 3 , 4 ) . Although it is a very common condition, its etiology has not been clearly defined yet 5 , 6 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface electromyography (sEMG) is a technique for measuring muscle activation onset, muscle activation duration, and muscle exertion level. It is commonly used by researchers [1,2] and physical therapists [3] as a tool for biofeedback [4], as an index of muscle fatigue [2], as a strength training tool [5], and as a motor learning and rehabilitation tool [6].…”
Section: Introductionmentioning
confidence: 99%